The complete chloroplast genome of Neolamarckia macrophylla (Rubiaceae). Issue 2 (2nd April 2020) - Shi, Shi; Larekeng, Siti Halimah; Lv, Pei; Nie, Yuying; Restu, Muhammad; Yang, Haijun
Abstract: Neolamarckia macrophylla (Rubiaceae) is a fast-growing tree with high economic value that is endemic to Sulawesi and Moluccas, Indonesia. Here, we presented the complete chloroplast (cp) genome sequence of N . macrophylla . The complete chloroplast genome is 155, 406 bp in size and includes a large single-copy region (86, 013 bp), a small single-copy region (18, 063 bp), and a pair of IR regions (25, 665 bp each). A total of 128 genes were predicted, including 8 rRNA, 36 tRNA, and 84 protein-coding genes. Phylogenetic analysis based on 11 plant species chloroplast genomes indicated that the genus Neolamarckia was monophyletic which clustered as a sister group to Antirhea chinensis . These complete chloroplast genomes can be subsequently used for valuable species research of Rubiaceae.